Pilihan Hidup Untuk Tidak Memiliki Keturunan (Childfree) dalam Ikatan Perkawinan - Mella Amanda Nuraini; Kanaia Brahmantia Hermanu; Naila Praba Kirana; Farras Eknu Albin; Risqi Budi Santoso; Baidhowi (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze Islamic legal perspectives on the decision of married couples to choose not to have children (childfree) by reviewing sharia arguments, interpretations of scholars, and the resulting social and legal implications. The childfree phenomenon is a contemporary issue that is increasingly being discussed, especially among the younger generation of ubanites in Indonesia. This decision is driven by various factors such as economic conditions, physical and mental health, enviromental awareness, career orientation, and lifestyle. The study was conducted using a qualitative-descriptive approach and the data obtained through library research methods. From an Islamic Legal perspective, this lifestyle choice is controversial because it is directly related to the maqāṣid al-sharīʿah, particularly the aspect of hifẓ al-nasl (preserving offspring). Previous research has explain that non-permanent contraceptive practices are permissible as long as there is the consent of the couple and do not cause harm. However, permanent contraceptive suc as vasectomy or tubectomy are considered contrary to Islamic law. The Indonesian Ulama Council (MUI) has also emphasized that permanent contraceptive measures are not permitted because the contradict the purpose of sharia to preserve offspring. Thus, Islamic law allows for ijtihad and deliberation in addressing the phenomenon of childfree, while still emphasizing that safeguarding offspring is a crucial part of the primary objective of sharia. This study aims to contribute academically to the discourse on Islamic legal flexibility in responding to evolving social realities, highlighting the dynamic interplay between normative principles and contemporary challenges.